BEEL FISHERIES RESOURCE MANAGEMENT AND IMPACT ON LIVELIHOOD STATUS OF PEOPLE IN MAJULI ISLAND OF ASSAM - Barik, Nagesh K; Sharma, Kishor K (Journal of the Inland Fisheries Society of India, 2016)
The paper deals with the fisheries resources, existing institutions and nature of livelihoods dependence in the MajuliÂ island of Assam. The local fishers, fishers from outside and local non-fishers had different level of dependence andÂ varied livelihood compositions. The share of the fishers in fishing was reported to be 50% with varying degree of costÂ sharing and entry fees. In terms of cost, the lease was most important (37.3 to 71.4 %), followed by transaction costÂ (14.3 to 20.3%). The expenses on enhancement measures were very low. Managers obtained profit of 1.5 times that ofÂ cost. The marketing of fish was not found to be a problem. The study suggested urgent need for up gradation of theÂ information available for proper planning towards fisheries development in the island.